A Rare Case of Primary Vulvar Diffuse Large B‐Cell Lymphoma: A Case Report - M. Singh; S. Ngakhusi; A. Shrestha; P. Subedi; K. Khadka; H. P. Dhakal (Clinical Case Reports)
ABSTRACT Primary vulvar diffuse large B‐cell lymphoma is a diagnostically challenging malignant tumor due to its low incidence and diverse clinical presentations. It has a good prognosis and is usually radio‐chemotherapy‐responsive. This case report emphasizes considering lymphoma as a differential in vulvar inflammatory conditions.